The Diminishing Agency of Urbanised Alevis Against the Rise of Political Islam in Turkey - Onay, Ozge (Poligrafi, 2021)
This paper critically examines the diminishing agency of the first-urbanised Alevi generation vis- à-vis the Justice and Development Party (AKP) and their sectarian agenda mediated by political Islam. The conceptual position is underpinned by Foucault’s concept of governmentality and theory of agency in broader cultural terms. These theoretical frameworks interweave to present a rich and complex set of snapshots that document the first-urbanised Alevi generation’s decreasing possibilities of action in the urban context. Accordingly, the empirical data that informs this piece has been collected by a series of qualitative and semi-structured interviews with the first-urbanised Alevi generation, children of those who migrated to urban areas in the 1960s and wittingly or unwittingly kept their identities undisclosed to varying degrees. Those interviewed come from a range of different professional backgrounds, with the only common point being that they have spent their childhoods and adult years in Istanbul, Turkey. Through a close engagement with the empirical material, this paper addresses the effects of the AKP’s Sunnification process centring around political Islam on the first generation urbanised Alevis and to what extent the systemic nature of this process attenuates or takes away their agency in the urban context. The account is focused around three key themes including daily life, institutional forms of discrimination and the workplace.